2015
DOI: 10.1021/jacs.5b03048
|View full text |Cite
|
Sign up to set email alerts
|

Enlightening the Mechanism of Copper Mediated PhotoRDRP via High-Resolution Mass Spectrometry

Abstract: The initiation mechanism of photochemically mediated Cu-based reversible-deactivation radical polymerization (photoRDRP) was investigated using pulsed-laser polymerization (PLP) and high-resolution mass spectrometry. The variation of the catalyst composition and ESI-MS analysis of the resulting products provided information on how initiator, ligand, copper species, and monomer are interacting upon irradiation with UV light. A discussion of the results allows for a new postulation of the mechanism of photoRDRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 48 publications
4
103
0
Order By: Relevance
“…33 Additionally, electrochemical studies have shown RAFT agents similar to those employed herein (i.e. In a recent publication focused on elucidating the mechanism of Cu-based Pi-RDRP it was illustrated that electron transfer from an amine ligand identical to the amine employed in this study (i.e.…”
mentioning
confidence: 65%
“…33 Additionally, electrochemical studies have shown RAFT agents similar to those employed herein (i.e. In a recent publication focused on elucidating the mechanism of Cu-based Pi-RDRP it was illustrated that electron transfer from an amine ligand identical to the amine employed in this study (i.e.…”
mentioning
confidence: 65%
“…25 To realize a visible light absorbing PC we explored a core substituted phenoxazine derivative. Computations predicted that PC 5 , possessing 4-biphenyl core substitutions, would be an excellent target PC with 3 PC* possessing a strong reduction potential and spatially separated SOMOs, while 1 PC would exhibit an absorbance profile in the visible spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of photoATRP with Cu as the catalyst has been the subject of some debate . Although detailed discussions of the mechanism are beyond the scope of this review, we will briefly summarize some of the key features of this mechanism.…”
Section: Mechanistic Considerations In Photoinduced Atrp (Photoatrp)mentioning
confidence: 99%